Enhancing System Security Through NFC (Near Field Communication) Technology - Siregar, Alviansyah; Ramadani, Anggun; Ramadhani, Dhea; Gultom, Joel Erwin; Peranginangin, Sinek Mehuli Br; Ginting, Meiliyani Br (JCEIT: Journal of Computer Engineering and Information Technology, 2024)
Abstract: A safe is a tool used to store valuables such as money, jewelry, securities, and so on. The crime rate is increasingly high in this country, especially the crime rate of theft, which encourages people to create safes with extra security systems. To achieve a security system that has double or layered security requires sophisticated technology. The technology used in this safe security system uses NFC (Near Field Communication), keypad. By using NFC as a card reader, a special password has been given which can only be read by NFC. Meanwhile, using an Arduino Uno as a microcontroller and a password to access the safe door is very difficult to duplicate. Keywords: NFC, Near Field Communication, Arduino Uno, Security System REFERENCES Aisuwarya, R., Putra, R. A., & Fatimah, F. (2023). Near Field Communication (NFC) Untuk Sistem Recording Data. Duha, T. (2022). Sistem Informasi Penjualan Berbasis Web. Penerbit Qiara Media. Hadiatullah, D. R. (2023). Employee Presence Design Based on Near Field Communication (Nfc). J-Icon: Jurnal Komputer Dan Informatika, 11(1), 7–13. Musman, A. (2021). Berdamai dengan Efek Negatif Medsos: Cara Terhebat untuk Terbebas dari Online Bullying, FOMO, atau Hoaks dengan Membiasakan Kebiasaan Baik di Media Sosial. Anak Hebat Indonesia. Muthohir, M., & Prayogi, S. (2021). Prototype Sistem Keamanan Brankas Menggunakan Teknologi RFID Berbasis Arduino Uno. Jurnal Manajemen Informatika & Teknologi, 1(2), 97–106. Raudiah, M., & Elfizon, E. (2020). Perancangan Keamanan Brangkas Berbasis Arduino dan Android. JTEIN: Jurnal Teknik Elektro Indonesia, 1(2), 246–250. Saptono, M. P., & Sumbiaganan, A. (2020). Lpg Gas Leakage Prototype Based on Atmega328 and Lcd Microcontroller As Information Media. Electro Luceat, 6(1), 82–92. Sari, W. E., & Syahwin, S. (2022). Prototipe Sistem Keamanan Brankas Berbasis Arduino Menggunakan Android. Sudo Jurnal Teknik Informatika, 1(4), 154–162.